The effects of heat exposure on tropical farm workers in Malaysia: six-month physiological health monitoring - How, Vivien; Singh, Shyamli; Dang, Thinh; Lim, Fang Lee; How, Ran Guo (Taylor and Francis, 2022)
Farmers in tropical countries have been impacted by slow-onset heat stress. By comparing the nature of farming activities performed by conventional farmworkers and agroecological farmers, this study examined the changes in physiological health in responses to heat exposure through a six-month longitudinal study. Throughout the six-month follow-up period, the heat stress index (HSI), physiological strain indices (PSI), and physiological health parameters (BMI, blood glucose level, blood cholesterol level, uric acid level) were measured and repeated every two-month. Physiological parameters were recorded twice daily, before and during their first lunch break. This study found that slow-onset heat stress affects farmers differently. The health of agroecological farmers is more resistant to slow-onset extreme temperatures. Pre-existing metabolic health effects from pesticide exposure make conventional farmers more susceptible to extreme temperatures, delaying their bodies’ adaptation to rising temperatures.